Miejsca konfliktu w poetyckich mikrohistoriach. O najnowszych wierszach autorek polskich i ukraińskich (Heteroglossia – studia kulturoznawczo-filologiczne, 2024)
The article analyzes selected concretized conflict sites in the latest Polish and Ukrainian women’s poetry as well as the subjective experience of oneself within history and in relation to it. The poetic proposals of microhistories go beyond the traditional aspects of constructing narratives about history, activating a subjective perspective and privileging the microscale. They confirm that the drama of shared existence recorded by “The Grand History” is just as significant as the drama of individual existence which, in the official version, would be doomed to oblivion. The article signals two types of conflict sites: the first – a vivid depiction dominated by a void that nothing can occupy; the second – existing places that have been repurposed, serving a function different from the original one. The exemplifying material consists of texts by contemporary Polish authors (Anna Frajlich, Julia Hartwig and Anna Augustyniak) and of poems by Ukrainian female poets which appeared in three bilingual series of the Ukrainian Poetry Library titled “In the Face of War” (published between 2022-2023).